Baseball Fans’ Evaluations of Robot Umpire: The Perspective of Human-Robot Interaction - Min Young Lee; Se-Young Park; Bomin Kim; Wonseok(Eric) Jang (Ch'eyuk kwahak yŏn'gu, 2022)
PURPOSE The current study examined how baseball fans evaluate a robot umpire from the perspective of the human-robot interaction. In particular, this study examined whether baseball fans evaluated more positively a robot umpire depending on whether a robot or a human umpire has the final authority to make ball-strike decisions, when the ball-strike decision contradicts with each other. Furthermore, the different types of expertise (baseball vs. image analysis) embedded in robot umpire and fans’ levels of technology adoption were used to examine the relationship between umpire type and evaluations of robot umpire. METHODS This study used 2 (final decision maker: robot vs. human umpire) by 2 (different types of expertise embedded in robot umpire: baseball vs. image analysis) by 2 (different levels of technology adoption: low vs. high) between-subjects design. RESULTS The results indicated that when a robot umpire had the final authority to make ball-strike decisions, baseball fans evaluated more positively the adoption of robot umpire, when image analysis expertise was embedded in the robot umpire rather than baseball expertise. Meanwhile, baseball fans evaluated more positively the adoption of robot umpire when baseball expertise was embedded in a robot umpire rather than image analysis expertise. CONCLUSIONS The current study provides meaningful implications regarding how to design an effective system for the operation of robot umpire in baseball.